2018
DOI: 10.7326/m17-2219
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Physicians and Skilled Home Health Care Agencies in the Certification of Medicare Beneficiaries' Plans of Care: Results of a Nationally Representative Survey

Abstract: National Institute on Aging and National Institute of Mental Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Policy solutions have traditionally been directed at rationalizing payment across populations, geography, setting, and time (27–29). Our study contributes to an emerging body of evidence emphasizing the need to better coordinate health care and community-based long-term services and supports (30, 31) and the potential cost savings of assessing and addressing the care needs of high-risk sub-populations (3235).…”
Section: Discussionmentioning
confidence: 92%
“…Policy solutions have traditionally been directed at rationalizing payment across populations, geography, setting, and time (27–29). Our study contributes to an emerging body of evidence emphasizing the need to better coordinate health care and community-based long-term services and supports (30, 31) and the potential cost savings of assessing and addressing the care needs of high-risk sub-populations (3235).…”
Section: Discussionmentioning
confidence: 92%
“…In a recent study of generalist physicians commonly engaged with skilled home health recipients, 78% reported rarely or never interacting with skilled home health clinicians. 6 While skilled home health offers important clinical services otherwise difficult to access by mobility-impaired people, no study to date has convincingly demonstrated the benefit of skilled home health. A recent study indicated that posthospitalization increases in continuity of care with primary care providers was associated with significantly fewer hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians and other providers vary in their involvement in coordinating care of the patient with skilled home health services. 6 In HBMC, health care providers (e.g. physicians, nurse practitioners, or physician assistants) and interdisciplinary care teams provide longitudinal primary or palliative care to individuals at home.…”
Section: Introductionmentioning
confidence: 99%
“…Better information communication will improve patient care by reducing missed clinical opportunities and providing research data for hospitalization risk predictive analytics. Studies highlight shortcomings in patient information communication along transitions in care [ 1 ], especially to home health care and between home health care and physicians [ 2 , 3 ], which are impediments to care coordination [ 1 ]. This inadequacy occurs in the United States [ 4 ] (US) and abroad [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A solution is electronic transmission of patient information [ 1 , 3 , 13 ] between electronic health record systems, and to embed home health care information into the routine outpatient clinical workflow for information to be more timely and accurate [ 1 , 3 ]. This communication necessitates implementation of reference terminologies (data standards) along the care transition.…”
Section: Introductionmentioning
confidence: 99%